Digital Traces: New Data, Resources, and Tools for Psychological-Science Research. (December 2019) - Rafaeli, Anat; Ashtar, Shelly; Altman, Daniel
New technologies create and archive digital traces —records of people's behavior—that can supplement and enrich psychological research. Digital traces offer psychological-science researchers novel, large-scale data (which reflect people's actual behaviors), rapidly collected and analyzed by new tools. We promote the integration of digital-traces data into psychological science, suggesting that it can enrich and overcome limitations of current research. In this article, we review helpful data sources, tools, and resources and discuss challenges associated with using digital traces in psychological research. Our review positions digital-traces research as complementary to traditional psychological-research methods and as offering the potential to enrich insights on human psychology.